Finite dimensional vertex - Mikhailov, Andrei [UNESP] (Springer, 2011)
The spectrum of linearized excitations of the Type IIB SUGRA on AdS(5) x S-5 contains both unitary and non-unitary representations. Among the non-unitary, some are finite-dimensional. We explicitly construct the pure spinor vertex operators for a family of such finite-dimensional representations. The construction can also be applied to in finite-dimensional representations, including unitary, although it becomes in this case somewhat less explicit.
Keywords: Superstrings and Heterotic Strings; AdS-CFT Correspondence; Conformal Field Models in String Theory